Specificity of the metabolic signatures of fish from cyanobacteria rich lakes. (July 2019) - Sotton, Benoît; Paris, Alain; Le Manach, Séverine; Blond, Alain; Duval, Charlotte; Qiao, Qin; Catherine, Arnaud; Combes, Audrey; Pichon, Valérie; Bernard, Cécile; Marie, Benjamin
Abstract: With the increasing impact of the global warming, occurrences of cyanobacterial blooms in aquatic ecosystems are becoming a main worldwide ecological concern. Due to their capacity to produce potential toxic metabolites, interactions between the cyanobacteria, their cyanotoxins and the surrounding freshwater organisms have been investigated during the last past years. Non-targeted metabolomic analyses have the powerful capacity to study simultaneously a high number of metabolites and thus to investigate in depth the molecular signatures between various organisms encountering different environmental scenario, and potentially facing cyanobacterial blooms. In this way, the liver metabolomes of two fish species ( Perca fluviatilis and Lepomis gibbosus ) colonizing various peri-urban lakes of the Île-de-France region displaying high biomass of cyanobacteria, or not, were investigated. The fish metabolome hydrophilic fraction was analyzed by 1 H NMR analysis coupled with Batman peak treatment for the quantification and the annotation attempt of the metabolites. The results suggest that similar metabolome profiles occur in both fish species, for individuals collected from cyanobacterial blooming lakes compared to organism from non-cyanobacterial dominant environments. Overall, such environmental metabolomic pilot study provides new research perspectives in ecology and ecotoxicology fields, and may notably provide new information concerning the cyanobacteria/fish ecotoxicological interactions. Graphical abstract: Image 1 Highlights: The liver metabolomes of fish from cyanobacterial-dominated ponds were investigated. Cyanobacterial metabolites were only be detected in cyanobacterial dominated ponds. The metabolomes of the 2 fish species exhibit similar correlation with cyanobacteria occurrence. Correlations between the levels of some metabolites and phycocyanin or pH were observed.